Tetraamminecopper(II) Nitrate and Its Effects on Ammonium Nitrate(V) - Künzel, Martin; Vodochodský, Ondřej; Matyáš, Robert; Jalový, Zdeněk; Pachman, Jiří; Maixner, Jaroslav (Institut Przemyslu Organicznego, 2017)
Tetraamminecopper(II) nitrate(V) (TACN) is a complex copper salt which is easily formed when ammonium nitrate (AN) comes into contact with copper. It is considered to be an unwanted contaminant of AN because of its sensitivity to mechanical stimuli and significant explosive properties. The formation of TACN by the reaction of copper with molten ammonium nitrate(V) was demonstrated by powder diffraction. Friction and impact sensitivity testing was performed and field experiments were then conducted to reveal the detonation parameters of TACN and its initiation capability towards ammonium nitrate. The dependence of the detonation velocity on charge diameter was revealed and the ideal detonation velocity of 3500 m.s(-1) at 0.87 g.cm(-3) was measured. AN with the addition of 16 wt.% of TACN was found to detonate when initiated with a small booster charge. Moreover, TACN was able to initiate detonation in fertilizer grade ammonium nitrate(V) under massive steel confinement. TACN should be therefore considered as a possible contributory initiation source in some large scale accidents. In this article, some properties of TACN are revealed which could be useful for the investigation of accidents.
Dusičnan tetraamminměďnatý a jeho vlivy na dusičnan amonný
Keywords: ammonium nitrate; complex salt; copper; detonation; initiation; dusičnan amonný; komplexní sůl; měď; detonace; iniciace